The Historical Roots of Visual Analog Scale in Psychology as Revealed by Reference Publication Year Spectroscopy - Yeung, Andy Wai Kan; Wong, Natalie Sui Miu (Frontiers in Human Neuroscience, 2019)
Background: Many researchers have been using the visual analogue scale (VAS) to acquire psychometric measurements from participants. Several recent studies have consistently pointed to Hayes and Patterson (1921) as the origin of the VAS method. The primary objectives of the current study were to identify the historical root of VAS by cited reference analysis and confirm if it was Hayes and Patterson (1921). Methods: The Web of Science database was searched to identify psychology papers dealing with VAS. The full records and their cited references were extracted and imported into CRExplorer for further analysis. A “reference publication year spectroscopy” (RPYS) was plotted to identify the seminal references. Results: We analyzed 32,569 references cited by 958 articles. There were 21 RPYS peaks ranging from year 1921 to 2007. We were able to identify Hayes and Patterson (1921) from the first peak. Furthermore, we were able to identify a total of seven seminal references that are directly relevant to VAS. Two of them were related to “graphic rating method”, three were VAS-validation studies, one was a review on the usage of VAS, and one compared reported results using VAS and Likert scale. Conclusions: Cited reference analysis with a RPYS plot succeeded in identifying and confirming Hayes and Patterson (1921) as the origin of VAS. This method has overcome the limitations of conventional citation analysis, namely the issues of being not indexed, not identified by pre-defined search keywords, and not being all-time most cited.